2021
DOI: 10.3389/fpubh.2021.665985
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Storey of Buildings and Fall Risk

Abstract: Purpose: This study examined the association between storey of building and fall risk in older adults' residences and residents' level of fear of falling.Methods: The National Health and Ageing Trends Study (NHATS) collected information that would provide an understanding of basic trends people aged 65 years and older. Using a longitudinal survey, the present study employed the first round of NHATS data that was collected in 2011. In the first round, 12,411 participants were enrolled, and 8,077 interviews were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In older adults, falls impose major health, economic, and societal burdens ( 16 ). Falls are the leading cause of injury in the elderly population ( 36 ). A serious fall could result in decreased independence and reduced QOL ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In older adults, falls impose major health, economic, and societal burdens ( 16 ). Falls are the leading cause of injury in the elderly population ( 36 ). A serious fall could result in decreased independence and reduced QOL ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Falls are the leading cause of injury in the elderly population ( 36 ). A serious fall could result in decreased independence and reduced QOL ( 36 ). Hip fracture, in particular, is a serious and devastating consequence of falling in older individuals ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty-two observational studies investigated stroke/TIA and falls. Forty-four reported a significant association: 42 positive, QA 7.0 (range 4–10) ( 32 , 37 , 43 , 54 , 57 , 59 , 62 , 64 , 66 , 72 , 73 , 76–78 , 82 , 87 , 89 , 93 , 101 , 104 , 147 , 154 , 155 , 158 , 163 , 167 , 170–172 , 176 , 183 , 192–202 ); 2 negative, QA 7, 7 ( 203 , 204 ). Thirty-seven studies reported no association: QA 7.2 (range 4–10) ( 31 , 33–35 , 38 , 39 , 41 , 51 , 52 , 56 , 60 , 61 , 65 , 67 , 69 , 71 , 80 , 81 , 83 , 85 , 88 , 90 , 95 , 106 , 107 , 112 , 126 , 129 , 164–166 , 173 , 205–209 ) ( Supplementary Table 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty observational studies investigated general cardiovascular disease (unspecified) and falls. Seventeen studies reported no association: QA 7.2 (range 5–10) ( 35 , 38 , 53 , 54 , 64 , 82 , 86 , 89 , 109 , 112 , 125 , 126 , 156 , 209–212 ). Thirteen reported a positive association: QA 6.9 (range 4–8) ( 47 , 65 , 66 , 69 , 74 , 94 , 102 , 163 , 172 , 177 , 206 , 213 , 214 ) ( Supplementary Table 13 ).…”
Section: Resultsmentioning
confidence: 99%